2020
DOI: 10.1080/19476337.2020.1743762
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer potential of dihydrocaffeic acid: a chlorogenic acid metabolite

Abstract: Chlorogenic acid is a well-known nutraceutical, but it is extensively metabolized by the body. More valuable information can be obtained from its metabolites. Dihydrocaffeic acid is a metabolite of chlorogenic acid and has shown antioxidant, cardioprotective, and neuroprotective effects; however, information about its anticancer activity is very scarce. Therefore, the main objective of this study was to determine the anticancer potential of dihydrocaffeic acid. The cancer cell lines used were MCF-7, Hep-G2, PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…In another study, the anticancer potential of dihydrocaffeic acid as a metabolite of chlorogenic acid using several cancer cell lines, including MCF7, HepG2, PC3, and HCT116, was explored. The authors found dihydrocaffeic acid to be significantly more cytotoxic to all cancer cell lines except Hep-G2, with a cytotoxic dose ranging between 162 and 390 M in PC3 [ 68 ]. In a study on the effectiveness of chlorogenic acid as a chemosensitizer in inhibiting tumor growth via metabolic pathways, this agent had the ability to stimulate and suppress many vital signaling pathways in cancer metabolism [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the anticancer potential of dihydrocaffeic acid as a metabolite of chlorogenic acid using several cancer cell lines, including MCF7, HepG2, PC3, and HCT116, was explored. The authors found dihydrocaffeic acid to be significantly more cytotoxic to all cancer cell lines except Hep-G2, with a cytotoxic dose ranging between 162 and 390 M in PC3 [ 68 ]. In a study on the effectiveness of chlorogenic acid as a chemosensitizer in inhibiting tumor growth via metabolic pathways, this agent had the ability to stimulate and suppress many vital signaling pathways in cancer metabolism [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, chlorogenic acid is recognized both for its nutritional and health benefits. Its activity against human breast, lung, colon, bone, and kidney cancers was demonstrated in vitro [ 28 ], while an in vivo study found antitumoral activity against colon cancer in rats [ 29 ]. Vanillic acid inhibited cell proliferation through a G1 phase arrest and an angiogenesis suppression, the antitumor activity was confirmed in a murine xenograft model with no apparent toxicity to the animals [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In cancer biology, reactive oxygen species (ROS) are known as a double-edged sword, because the imbalance or accumulation of ROS lead to both the survival and death of cancer cells, respectively [ 44 , 45 ]. Particularly, it has been shown that ROS enhances the activation of the Raf/MEK/ERK signaling pathways to promote cancer cell survival, cell proliferation, cell migration, and differentiation [ 46 ], whereas ROS accumulation via pro-oxidants under severe oxidative stress conditions leads to apoptosis and cell death [ 47 ]. BF-treated SK-MEL-2 cells exhibited similar levels of ROS as compared with mock control ( Figure 3 ), suggesting that inactivation of MEK by BF-treatment ( Figure 2 A) was not mediated by ROS levels.…”
Section: Resultsmentioning
confidence: 99%